A Network Analysis of the Relationships Between Behavioral Inhibition/Activation Systems and Problematic Mobile Phone Use - Gao, Lingfeng; Zhao, Wan; Chu, Xiaowei; Chen, Haide; Li, Weijian (Frontiers in Psychiatry, 2022)
Background: It is of great concern to society that which individuals are vulnerable to problematic mobile phone use (PMPU). However, there are a few studies in the field evaluating associations between behavioral inhibition/activation systems (BIS/BAS) and PMPU, and the results have been inconsistent. This study aimed to explore the relationships between BIS/BAS and PMPU by network analysis. Methods: A total of 891 young adults participated in the study. BIS/BAS and PMPU were assessed by using the behavioral inhibition and activation systems scale and smartphone application-based addiction scale, respectively. The structure of the BIS/BAS-PMPU network was characterized using “strength”, “closeness” and “betweenness” as centrality indices. Edge-weight accuracy and centrality stability were tested using a bootstrap procedure. Results: The network analysis showed that “mood modification”, “tolerance” and “withdrawal symptoms” had high centrality. In addition, the positive connection between BIS and “mood modification” or “tolerance” and between BAS-fun seeking and “mood modification” or “conflict” were also shown in the BIS/BAS-PMPU network. Conclusion: These findings shed light on the central and bridge components between the BIS/BAS and PMPU communities, providing new evidence relevant to potential mechanisms that account for how high-BIS or high-BAS individuals develop PMPU, and inspiring component-based PMPU prevention or interventions.